Efficient Detection of Long dsRNA in Vitro and in Vivo Using the dsRNA Binding Domain from FHV B2 Protein - Monsion, Baptiste; Incarbone, Marco; Hleibieh, Kamal; Poignavent, Vianney; Ghannam, Ahmed; Dunoyer, Patrice; Daeffler, Laurent; Tilsner, Jens; Ritzenthaler, Christophe (Frontiers in Plant Science, 2018)
Double-stranded RNA (dsRNA) plays essential functions in many biological processes, including the activation of innate immune responses and RNA interference. dsRNA also represents the genetic entity of some viruses and is a hallmark of infections by positive-sense single-stranded RNA viruses. Methods for detecting dsRNA rely essentially on immunological approaches and their use is often limited to in vitro applications, although recent developments have allowed the visualization of dsRNA in vivo. Here, we report the sensitive and rapid detection of long dsRNA both in vitro and in vivo using the dsRNA binding domain of the B2 protein from Flock house virus. In vitro, we adapted the system for the detection of dsRNA either enzymatically by northwestern blotting or by direct fluorescence labeling on fixed samples. In vivo, we produced stable transgenic Nicotiana benthamiana lines allowing the visualization of dsRNA by fluorescence microscopy. Using these techniques, we were able to discriminate healthy and positive-sense single-stranded RNA virus-infected material in plants and insect cells. In N. benthamiana, our system proved to be very potent for the spatio-temporal visualization of replicative RNA intermediates of a broad range of positive-sense RNA viruses, including high- vs low-copy number viruses.